"Continued criticism today over the extravagance of Governor General Adrienne Clarkson's Circumpolar tour. Clarkson defended the tour saying it was a way to introduce Canada to the northern world. [.] - Harrop, Graham (Globe and Mail, 2003)
"Continued criticism today over the extravagance of Governor General Adrienne Clarkson's Circumpolar tour. Clarkson defended the tour saying it was a way to introduce Canada to the northern world. One person at a time.President Putin, you've met the Edmonton Eskimos?"